Sintagmatica morfonologică a radicalului flexionar nominal: tipuri de structură - Cychnerski, Tomasz (Studia Romanica Posnaniensia, 2014)
This paper presents the results of a detailed analysis of the Roumanian nominal inflectional root. Its aim is to describe the morphonological types of root and their syntagmatic relevance. In this way, seven relevant types of the nominal inflectional root are defined according to its final phonological segments: unmarked vowel root, /u/ root, unmarked consonant root, /j/ root, consonant+liquid consonant root, palatal consonant root and velar consonant root.